Deciphering Prime Number Distribution: Insights from Natural Numbers - Moussa, Ouannas (Mathematics and Computer Science: Contemporary Developments Vol. 8, 2024)
In this paper I present the distribution of prime numbers which was treated in many researches by studying the function of Riemann; because it has a remarkable property; its non trivial zeros are prime numbers; but in this work I will show that we can find the distribution of prime numbers on remaining in natural numbers only.